Elevated levels of serum glucose, triglyceride, and liver enzymes in a rat model of 7,12 dimethylbenz[a]anthracene (DMBA)-induced carcinogenesis - Ika Yustisia; Padlianah Padlianah; Mutmainah Arif; M. Husni Cangara (Journal of Biomedicine and Translational Research, 2022)
ABSTRACT Background: Uncontrolled cell proliferation in cancers has a high requirement of energy and biosynthetic substrates. Glucose and triglycerides are the main source of energy as well as the primary building blocks for forming cellular components of mammalian cells.Objective: This study aims to evaluate the shifting of serum glucose, triglyceride, and nitrogen wastes in the form of urea and creatinine levels; and liver enzymes levels, alanine transaminase (ALT) and aspartate aminotransferase (AST), in rat model carcinogenesis with a single dose of 7,12-dimethylbenzanthracene (DMBA) for 16 weeks observation..Methods: The experimental animals of Rattus norvegicus strain Sprague Dawley were divided into two groups, namely the control group and the DMBA-induced group. A blood chemistry examination was carried out at weeks 4, 8, 12, and 16 post-induction using a spectrophotometer. In addition, observation of breast tumor formation and histological examination of the tumor and organs, including liver, lung, intestine, and kidney, were performed to confirm cancer formation.Results: Five of the six experimental rats (83.3%) induced by DMBA experienced breast and lung cancer formation accompanied by continuous weight loss starting at week 10 after induction. Serum glucose levels increased significantly at weeks 12 and 16 after induction, while serum triglyceride, ALT, and AST levels increased significantly from week 4 after induction until the end of the experiment. Serum urea levels did not show a significant difference from the control group. Nonetheless, creatinine decreased at the last examination.Conclusion: Elevated serum glucose, triglycerides, ALT, and AST levels escorted the chemical carcinogen-induced cancer development. Studies at the clinical level are needed to prove whether abnormally elevated of these blood chemistry levels can be used to detect the presence of cancer early.Keywords:DMBA, breast cancer, lung cancer, cancer metabolism.